A utilização do planejamento estratégico situacional PES como instrumento de abordagem, processamento e gestão tecnopolítico de conflitos socioambientais urbanos: estudo de caso do parque linear nascentes do Ribeirão do Jaguaré - Roic, Ernani (2013)
Environmental conflicts are a reality that tends to occupy more space on the public agenda, both nationally and internationally, as it deepens the process of economic and social transformation of societies and their territories. This reality highlights the dispute for hegemony between different conceptions about ways of incorporating nature to satisfy material needs, symbolic and spiritual of individuals and communities. Relative to São Paulo, a city that, from the 1950s began to go through a process of broad and rapid urban expansion, linked to the implementation of public policies that prioritized the use and occupation of the more central regions of urban space, favored largely by road constructions, ultimately left considerable portion of the population, especially the poor, to the valley bottom. Front this scenario, the proposition of linear parks as a public policy, along with such areas, it becomes viable alternative to urban and environmental upgrading of the city, but not without environmental conflicts, in view of the presence of several actors, with different positions and diffuse interests against the use and occupation of these areas. This study aims to analyze a case of conflict environmental inserted in the proposed implementation of the Linear Park Headwaters Ribeirão Jaguaré (District Raposo Tavares - São Paulo - SP), taking as reference some elements of the methodology "Situational Strategic Planning - PES". The PES is a method of planning for and dealing with problems of a technical and political problems particularly ill-structured and complex, for which there exists a solution previously known and fit the environmental conflicts. This study, exploratory and qualitative, includes a comparative analysis of PES: a brief review of the literature on environmental conflicts and a sample of case studies of the use of PES and a list of mechanisms for solving problems involving environmental questions. Interviews were conducted with semi-structured scripts with the actors involved in the conflict in question, to characterize the initial situation and proposing measures to change the situation in the light of the PES. The results point to the possibility of using some technical and political PES, assigning greater intelligibility in approach, processing and management of environmental conflicts, and therefore a contribution to the improvement and / or development of public policies in the urban.